2015
DOI: 10.1093/ije/dyv096.287
|View full text |Cite
|
Sign up to set email alerts
|

Hormone Replacement Therapy and Oral Contraceptives and Risk of Oesophageal Adenocarcinoma: A Systematic Review and Meta-analysis.

Abstract: There is an unexplained strong male predominance in the aetiology of oesophageal adenocarcinoma (OAC). The hypothesis that oestrogens are protective, deserves attention. A potential protective influence of exogenous oestrogen exposure, that is, hormone replacement therapy (HRT) and oral contraceptives (OC) has been addressed only in studies of limited statistical power, and the individual studies have not provided conclusive results. We conducted a systematic literature search and meta-analysis on HRT and OC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
1
16
1
Order By: Relevance
“…Women using sex hormones, such as HRT after menopause and OC, may be less susceptible to EC. A recent meta‐analysis of five independent studies has implicated that OC and HRT use seemed to reduce the risk of EAC . On the contrary, no significant association between OC and HRT use and the risk of EAC was found in our meta‐analysis of six individual publications.…”
Section: Discussioncontrasting
confidence: 83%
“…Women using sex hormones, such as HRT after menopause and OC, may be less susceptible to EC. A recent meta‐analysis of five independent studies has implicated that OC and HRT use seemed to reduce the risk of EAC . On the contrary, no significant association between OC and HRT use and the risk of EAC was found in our meta‐analysis of six individual publications.…”
Section: Discussioncontrasting
confidence: 83%
“…Original studies examining MHT and risk of esophageal and gastric adenocarcinoma have typically been under‐powered, have mostly examined one or two cancers per study and arrived at inconsistent findings . However, meta‐analyses comparing ever‐users of MHT with non‐users have shown statistically significantly decreased relative risk estimates of esophageal adenocarcinoma, gastric adenocarcinoma and also of esophageal squamous cell carcinoma . We hypothesized that MHT decreases the risk of esophageal and gastric adenocarcinoma, but not of esophageal squamous cell carcinoma.…”
mentioning
confidence: 98%
“…Similar to our study although, Lu et al found no significant relationship for increasing number of children fathered. 23 In women, although results from individual studies have been inconsistent, pooled analyses have found positive associations for menopause 31 and inverse associations for breastfeeding, 31,32 longer years of fertility 33 and HRT use, 31,33,34 providing some support that endogenous and exogenous oestrogen exposure may lower oesophageal and gastric cancer risk in women. The weak evidence of an association between frontal baldness and gastric cancer risk is difficult to interpret and requires confirmation.…”
Section: Discussionmentioning
confidence: 99%